Training characteristics of Swedish adolescent biathletes - Kårström, A.; Laaksonen, M. S.; Björklund, G. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: At upper secondary school (USS) with a sport profile, late-adolescent athletes choose to specialize in one sport and balance an academic career while they aim to become a top-level athlete. Hence, the aim for this study was to examine the distribution in endurance training volume and intensity in two different performance groups of biathletes during their student-athlete pathway at USS.